2021
DOI: 10.25259/sni_837_2021
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular management of spontaneous intracranial pseudoaneurysms in a pediatric patient with Noonan syndrome. A mere coincidence or a possible association with the disorder?

Abstract: Background: Noonan syndrome (NS) is a rare autosomal-dominant neurodevelopmental disorder, which typically develops abnormalities of the craniofacial development and congenital heart defects. A number of cerebrovascular anomalies have also been occasionally described previously in the setting of NS. The assumption that NS can induce the formation of intracranial pseudoaneurysm (IAP) or the rupture of an already existing abnormality is yet unknown. Case Description: We encountered a rare case of a 9-year-ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Reported causes include Marfan's syndrome, fibromuscular dysplasia, vasculitis, rupture of true cerebral aneurysm, arteriovenous malformation, moyamoya disease, radiotherapy, and atherosclerosis. 3,4,7) This A B C patient had been taking medication for hypertension, and signs of atherosclerosis in the major vessels were observed, which can be hypothesized as the cause. However, hypertension and atherosclerosis are too common in older people to be useful diagnostic information.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Reported causes include Marfan's syndrome, fibromuscular dysplasia, vasculitis, rupture of true cerebral aneurysm, arteriovenous malformation, moyamoya disease, radiotherapy, and atherosclerosis. 3,4,7) This A B C patient had been taking medication for hypertension, and signs of atherosclerosis in the major vessels were observed, which can be hypothesized as the cause. However, hypertension and atherosclerosis are too common in older people to be useful diagnostic information.…”
Section: Discussionmentioning
confidence: 87%
“…3) Spontaneous intracranial pseudoaneurysms are rare, and if there are no other symptoms beyond epistaxis, they can be challenging to diagnose. 4,5) An untreated pseudoaneurysm can result in a mortality rate exceeding 50%. Thus, a delayed diagnosis and treatment of spontaneous pseudoaneurysm can result in lethal outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…It was decided to proceed with urgent endovascular repair to occlude the pseudoaneurysm and the mother artery using Glubran 2. The postoperative course presented no major complications, and the patient was fully conscious and cooperative, with no focal neurological deficits [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…CT angiography did not show the source of bleeding (arteriovenous malformations or aneurysms). Recently, Athanasiou et al [14] have reported a nine-year-old male with Noonan syndrome and a heterozygous missense mutation in the PTPN11 gene who had two intracranial pseudoaneurysms leading to episodes of intracerebral hemorrhage, which were successfully treated with endovascular embolization.…”
Section: Discussionmentioning
confidence: 99%